5. EVALUATION OF THE DIAGNOSTIC AND PROGNOSTIC VALUE OF PROCALCITONIN IN PATIENTS WITH SEPTIC SHOCK AT NGHE AN GENERAL FRIENDSHIP HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objectives: Procalcitonin was rated highest on all three criteria of diagnosis, prognosis and infection monitoring. Research objective: To evaluate the diagnostic and prognostic value of procalcitonin in patients with septic shock. Subjects and Methods: Cross-sectional descriptive study with analysis of 92 patients diagnosed with septic shock were admitted to the ICU department from July to October 2022. Results: At the time of septic shock, the serum procalcitonin concentration was greater than 10ng/ ml, the mean procalcitonin in the mortality group was higher than the survival group (p
Keywords: Septic shock, procalcitonin.